2013
DOI: 10.1088/0953-4075/46/11/115208
|View full text |Cite
|
Sign up to set email alerts
|

Multiple ionization of neon induced by Li3+and C3+projectiles: influence of projectile screening in the ionization and electron capture channels

Abstract: Neq + (q = 1,2,3,4) ionization and charge exchange cross sections (total electron capture, single electron capture and transfer ionization) in the collisions with Li3+, with energies between 100 and 900 keV amu−1, and C3+, with energies between 250 and 500 keV amu−1 are reported. Bare Li3+ projectiles give a key benchmark to study the role of projectile screening in collisions involving dressed projectile ions, and the measurements have shown a strong screening effect for all n-fold recoil ion charge states in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Figures 2-4 show our measured values of cross section ratio R k1 for C q+ -Ne (q = 1-3), the estimates from the present theory, and previous other groups' results. [29,30] this work Kirchner et al [29] Ihani et al [30] this work Kirchner et al [29] Ihani et al [30] this work Kirchner et al [29] Ihani et al [30] R31 R41 R21 It is clear that our experimental data and other groups' results are quantitatively accordant with the present results for R 21 and R 31 obtained from the ME-COBI model, and for R 41 , they are qualitatively consistent with the result from the present model. The experiment and the theory model both indicate that the cross section ratios for C q+ -Ne collision are strongly dependent on projectile energy.…”
Section: Theoretical Methodssupporting
confidence: 90%
“…Figures 2-4 show our measured values of cross section ratio R k1 for C q+ -Ne (q = 1-3), the estimates from the present theory, and previous other groups' results. [29,30] this work Kirchner et al [29] Ihani et al [30] this work Kirchner et al [29] Ihani et al [30] this work Kirchner et al [29] Ihani et al [30] R31 R41 R21 It is clear that our experimental data and other groups' results are quantitatively accordant with the present results for R 21 and R 31 obtained from the ME-COBI model, and for R 41 , they are qualitatively consistent with the result from the present model. The experiment and the theory model both indicate that the cross section ratios for C q+ -Ne collision are strongly dependent on projectile energy.…”
Section: Theoretical Methodssupporting
confidence: 90%
“…The main difference lies in the high-energy edge distribution, where the three projectile energies have different slopes in the general monotonic decrease trend (above 30 eV). Higher production of energetic H + ions occurs for lower projectile energies, where the double electron removal channels, in particular the electron capture with multiple ionization (transfer ionization), start to compete with the pure single-ionization channel [50,51].…”
Section: A Electrostatic Spectrometry Resultsmentioning
confidence: 99%
“…It was observed that the experimental results are independent of the hitting position of the product ions on the detector. The detection efficiency of the recoil-ion detector was observed to be independent of either the charge state or the energy of the particle hitting the detector, so that the ratio of counting rates is a measure of the intensity ratio of the ions [51,52].…”
Section: Methodsmentioning
confidence: 99%